Kesulitan Belajar Matematika Siswa Kelas VIII SMP Negeri 1 Telaga Dalam Pembelajaran Daring - Bagu, Nasir; Pomalato, Sarson W. Dj.; Abdullah, Abdul Wahab (Research in the Mathematical and Natural Sciences, 2025)
This study aims to identify the sources and causes of learning difficulties in mathematics among eighth-grade students at SMP Negeri 1 Telaga during online learning. A descriptive research method was employed, with data collected through a Likert-scale questionnaire and semi-structured interviews. The results revealed an average difficulty percentage of 53.40%, with the majority falling into the medium category. Unstable network conditions were identified as the primary source of difficulties (63.91%), while limited interaction and delivery of material were the main causes (59.06%). These findings provide valuable insights for teachers and schools in designing more effective online mathematics learning strategies.